TRANSFORMASI DINAMIKA SASTRA DAN SENI DALAM MASYARAKAT MUSLIM INDONESIA - Ahmad Ihsan Syarifuddin; Armiya Nur Lailatul Izzah, M.Pd (Institut Agama Islam Ngawi, 2021)
Abstract Art and literature are important elements in the history of the spread of Islam, especially in Indonesia, but the reality is that there are many differences among ulama, fuqaha, and among intellectuals about art and literature. In the perspective of Islamic Sufism, art is associated with Belief in God values, while literature as a medium for the spread of Islam which has beauty values. The absence of a definite instrument regarding Literature and Art causes arts and literature in Muslim society to be isolated and unable to develop. This paper will focus on researching literature, art and Islam in general, and how the journey of literature and art in the development of Islam, as well as seeing the extent to which literature and art can be called Islamic. This research uses descriptive analysis method. The paper ends with the conclusions that this paper is not meant to provide halal and haram or good and bad laws regarding literature and arts, but this article simply wants to describe the reality of the relationship between literature and art in the Islamic paradigm in Indonesia. Keywords: Literature, Art, Indonesian Islam